Efficient Red‐Emissive Organic Crystals with Amplified Spontaneous Emissions Based on a Single Benzene Framework. Issue 41 (30th August 2017) - Tang, Baolei; Wang, Chenguang; Wang, Yue; Zhang, Hongyu
Abstract: Red‐emissive fluorophores generally consist of large π‐extended systems and thus encounter the problem of serious fluorescence quenching in the solid state. A series of structurally simple compounds 2, 5‐bis(alkylamino)terephthalates 1 a –c are reported that consist of a very small π‐system (only a single benzene) but display efficient red emission in crystals. Crystal 1 a having a molecular weight of only 252 g mol −1 shows red emission with the maximum of 620 nm and a fluorescence quantum yield of 0.40. The unique emission property of crystal 1 a is mainly because of the planarization of skeleton dominated by the strong intramolecular hydrogen bonds and the packing structure with negligible π–π interactions contributed by the mini π‐system. Moreover, besides efficient red emission, high crystallinity with co‐planar facets endows crystal 1 a with significant amplified spontaneous emission. Abstract : Mini fluorophore : A π‐system based on a simple single benzene structure displays efficient red emission (maximum 620 nm, fluorescence quantum yield 0.40) in the crystal. The highly crystalline organic fluorophore shows amplified spontaneous emission (ASE) with a low threshold.